Mix design of concrete with recycled clay-brick-powder using the orthogonal design method - Ge, Zhi; Gao, Zhili; Sun, Renjuan; Zheng, Li (Construction & building materials, 2012)
► The effects of clay-brick-powder and mix proportion on concrete mechanical properties were evaluated. ► The strength of concrete containing clay-brick-powder could be close to or even higher than that of normal concrete. ► Addition of clay-brick-powder reduced elastic modulus. ► The optimal mix proportion of concrete containing clay-brick-powder depended on the desired property. This research studied the effect of clay-brick-powder (CBP) on concrete mechanical properties, including compressive strength, static elastic modulus, and flexural strength. The orthogonal experimental design method was used to study the significance sequence of all influencing factors, including water/cementitious material ratio, sand ratio, replacement level, and average particle size of the CBP. A total of 17 mixes were tested including one normal cement concrete as reference. The mixtures with CBP reach more than 50MPa and 20GPa for 28-day compressive strength and elastic modulus, respectively. The flexural strength ranged from 10 to 12MPa. Experiment results showed that recycled CBP could be used as partial replacement of cement in concrete. The optimal mix proportion was determined based on the experimental and orthogonal analysis.